Perceptions of professionals on energy efficiency in green building rating system for the aim of implementation in Sudan - Shikheldin, Hamror (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
In most countries of the world, 'Green-building' rating systems have transformed the sustainability of the built environment. The most important aspect of these is Energy use. Sudan, like many other developing countries, has yet to implement such guidelines in spite of their importance for energy conservation in the global development context. This research aimed to formulate assessment-criteria for energy-efficiency in a green-building rating system for Sudan. This was achieved by examining the perceptions of officials involved in implementing the Malaysian Green Building Index (GBI), as well as other professionals in the Sudanese building industry. A review and comparison of the information obtained helped to explore possible assessment-criteria for efficient and sustainable energy-use in Sudan. Furthermore, a survey assessing the practicality of adopting the Malaysian system in Sudan, was carried out. The findings and results of the study were encouraging, with the provision that the relevant bodies and officials were open to modifications and adjustments in the existing systems.